THE ROLE OF AN ACADEMIC LEAGUE IN HEALTH EDUCATION IN BASIC HEALTH UNITS IN A MUNICIPALITY IN GOIÁS: EXPERIENCE REPORT - Correia, Anna Kharolyna Aciole; Arcaminho, Ágda Karolyne Ferreira de; Ferreira, Brunna Emanuelly Gonçalves; Martins, Luana de Oliveira; Ramos, Thallita de Freitas; Ferreira, Shirley Kellen (CIPEEX, 2025)
An effective method for promoting health is education. With this tool, it is possible to promote quality care for patients and, consequently, foster bonds between professionals and the population. With this in mind, academic leagues contribute to the training of qualified professionals. In March, awareness campaigns on endometriosis and cervical cancer take place. The objective of this study was to report the experience of an academic league in promoting health education in a basic health unit in a municipality in Goiás, addressing the themes of March Lilac and March Yellow. This is a descriptive study of the experience report type. The development of this health education work with women allowed us to verify the importance of education in basic health units on women's health for promoting knowledge among the population. In addition, the opportunity to talk with patients provides a rich experience for quality training for students.